2018
DOI: 10.1038/s41564-018-0321-5
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic variation and strain-specific functional adaptation in the human gut microbiome during early life

Abstract: Summary The human gut microbiome matures toward the adult composition during the first years of life and is implicated in early immune development. Here, we investigate the effects of microbial genomic diversity on gut microbiome development using integrated early childhood datasets collected in the DIABIMMUNE study in Finland, Estonia and Russian Karelia. We show that gut microbial diversity is associated with household location and linear growth of children. Single nucleotide polymorphism (SNP)- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
175
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(190 citation statements)
references
References 74 publications
13
175
1
1
Order By: Relevance
“…Bifidobacterium bifidum, Bifidobacterium breve and Bifidobacterium longum, possess genetic adaptations to facilitate colonization of the infant gut (Matamoros et al, 2013;Milani et al, 2017b). Recently, a number of studies have presented comprehensive data showing that these three species can be maternally inherited by vertical transmission (Milani et al, 2015a;Duranti et al, 2017b;Vatanen et al, 2018;Moossavi et al, 2019). Further evidence has found that horizontal transfer of bifidobacterial DNA from mother to foetus may occur also via placenta (Satokari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bifidobacterium bifidum, Bifidobacterium breve and Bifidobacterium longum, possess genetic adaptations to facilitate colonization of the infant gut (Matamoros et al, 2013;Milani et al, 2017b). Recently, a number of studies have presented comprehensive data showing that these three species can be maternally inherited by vertical transmission (Milani et al, 2015a;Duranti et al, 2017b;Vatanen et al, 2018;Moossavi et al, 2019). Further evidence has found that horizontal transfer of bifidobacterial DNA from mother to foetus may occur also via placenta (Satokari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Because it uses sample-assembled genomes and full paired-read information there is greatly increased confidence that reads are aligned correctly, which improves the high resolution comparisons being made based on entire genomes. Many of these capabilities have been successfully implemented individually in previous studies 15,19,[30][31][32][33] . However, their simultaneous integration into a well-documented and easy to use pipeline allows substantially more rigorous detection of near-identical strains than the existing commonly used pipelines ( Figure 2 ) used in recent high-profile publications to quantify the ecologically critical process of microbiome transmission 14,34 .…”
Section: Discussionmentioning
confidence: 99%
“…[5,[22][23][24] Likewise, in adults, Firmicutes and Bacteroidetes are prominent in the gut, and metabolize dietary plant polysaccharides, which are otherwise indigestible by the mammalian host. Indeed, a mammalian host is unable to complete digestion of the entirety of food or to de novo produce all food-related vitamins that are critically important for a healthy living.…”
Section: Gut Microbes Are Essential For Food Digestionmentioning
confidence: 99%